Knowing About Anemia Does Not Guarantee That Young Women Are Not Anemic - Kuswati, Kuswati; Nurrasyidah, Rahmi (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: Anemia in adolescents will have an impact on decreased focus on learning, decreased physical fitness, impaired growth and development. Knowledge is the basis for someone to apply behavior. Objective: To determine the relationship between adolescent girls' knowledge about anemia and the incidence of anemia in Glodogan Village, Klaten Selatan, Klaten. Method: this is a cross sectional research. Carried out from July to December 2023. The sampling technique uses accidental sampling, about 39 samples were obtained. Hb measurements are then interpreted with the incidence of anemia in adolescent girls. Data analysis uses univariate and bivariate data analysis. Result: The majority of respondents (76.9%) are middle adolescents, about 13-17 years. The majority of respondents' education level is secondary education (56.4%). Upper arm circumference some respondents were abnormal (56.4%). Body Mass Index most of the respondents were normal (76.9%). Almost half of the respondents suffer from anemia (43.6%). More than half of the respondents had good knowledge (61.6%). Based on the test of two variables, it was found that there was no relationship between knowledge about anemia and the incidence of anemia, where as many as 23.1% of teenagers who had good knowledge suffered from anemia. Conclusion: There was no relationship between knowledge about anemia and the incidence of anemia. For further researcher, it is hoped to explore other factors that influence the incidence of anemia. Community health center is expected increasing community empowerment in preventing anemia.